Multiscale approach for modeling electron spectra induced by photons from solids. (21st December 2015) - Kövér, L.
Abstract : Physical and chemical phenomena reflected in electron spectra excited by photons from solids take place on very wide scales of space, time, and excitation energy, covering sometimes differences of many orders of magnitude. Therefore, the use of multiscale approaches seems to be promising when extracting information on electronic structure or chemical composition from such electron spectra. Following a summary of phenomena reflected in electron spectra induced from solids by photons and different type of models available for their interpretation, the challenges of characterization of advanced materials and the need for multiscale materials analysis and modeling will be discussed. Copyright © 2015 John Wiley & Sons, Ltd.